If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 27 = -5(5x + -8) Combine like terms: 13 + 27 = 40 40 = -5(5x + -8) Reorder the terms: 40 = -5(-8 + 5x) 40 = (-8 * -5 + 5x * -5) 40 = (40 + -25x) Add '-40' to each side of the equation. 40 + -40 = 40 + -40 + -25x Combine like terms: 40 + -40 = 0 0 = 40 + -40 + -25x Combine like terms: 40 + -40 = 0 0 = 0 + -25x 0 = -25x Solving 0 = -25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25x' to each side of the equation. 0 + 25x = -25x + 25x Remove the zero: 25x = -25x + 25x Combine like terms: -25x + 25x = 0 25x = 0 Divide each side by '25'. x = 0 Simplifying x = 0
| 6=1.12 | | 54+x=33.7 | | 6ln(6x)=24 | | 0.002+0.03=0.92 | | 85+5n=20 | | 0.4+1.3=15 | | 9x+18=9(x+2) | | y=7x-28+x | | 100000=20x+20000 | | 36-11x=-8x-39 | | -(x+3)+.75x+5=0 | | 6-(x+6)=6-3(x+4) | | 9-x=-3x+-3 | | -12+2=11 | | 4x^2=8x+16 | | 7-(8x-3)=-6x | | 0=-9x^2+6x+3 | | 8+3(x+2)=8(5+2x) | | 4x-136=3x+30 | | 24=9x+x^2 | | 5(x+2)=-3(x+2) | | w^2-4w+5=0 | | 7+3(18-13)= | | (3x-2)(x+10)=0 | | 7(x-9)=-8(x+1)+5 | | 60000=150x+5000 | | 94-6x=-80-12x | | 10000=150x+5000 | | 29+72+x=180 | | 4x+6(x-8)=5(x-1)-3 | | m/2+4=16 | | f(x)=-9x^2+6x+3 |